Cytotoxicity comparison between fluoride varnish and SDF in pulpal stem cells using MTT assay: an in vitro study - Manisha Bala Rathy; Mahesh Ramakrishnan (Romanian Journal of Stomatology)
Background and objectives. SDF and fluoride varnish have garnered attention for their ease of application and potential to address ECC, particularly in young children with limited cooperative abilities for traditional dental procedures. But the cytotoxicity of these materials are not yet studied extensively. Materials and methods. Extracted human primary molars of comparable size and with no visible cavitated carious lesions were collected. The teeth were stored for less than 30 days in 0.1% thymol solution at 23°C prior to the experiment. Each tooth was coated with fluoride varnish and SDF respectively. MTT assay was performed and cytotoxicity is evaluated. Results. The materials used in this study - SDF and fluoride varnish showed significantly lower cell viability compared to the control group. There was significantly higher cell viability in SDF samples compared to fluoride varnish. Conclusions. Within the limitations of the study, it is concluded that the cell viability of SDF is higher when compared with the fluoride varnish.